Preliminary observations and simulation of nocturnal variations of airglow temperature and emission rates at Pune (18.5°N), India. (November 2016) - Fadnavis, S.; Feng, W.; Shepherd, Gordon G.; Plane, J.M.C.; Sonbawne, S.; Roy, Chaitri; Dhomse, S.; Ghude, S.D.
Abstract: Preliminary observations of the nocturnal variations of the OH(6-2) and O2b(0-1) nighttime airglow in the mesosphere and lower thermosphere are investigated in the context of tidal influence for the tropical latitude station Pune (18.5°N, 73.85°E). This is the only tropical Spectral Airglow Temperature Imager (SATI) station where the tidal variations of mesosphere and lower thermosphere (MLT) temperature have been determined from ground based SATI observations. The SATI observations obtained since October 2012 reveal the influence of the migrating semidiurnal tides during solstice at this tropical station. There is variability in amplitude and phase obtained from SATI observations. In this paper, SATI observations on 10 Dec 2012 and 3 March 2013 are compared with Whole Atmosphere Community Climate Model (WACCM) simulations. The amplitude of semidiurnal tides is ~25 K/30 K on 10 Dec 2012 during solstice for OH/O2 temperature. During equinox SATI data indicates existence of semidiurnal tide also. The airglow observations are compared with simulations from the WACCM. The model underestimates the amplitude of the semi diurnal tide during equinox (1.6 K/2.7 K at 87 km/96 km) and solstice (~3.8 K/4.8 K at 87 km/96 km) for these days. The reason may be related to dampening of tides in the model due to the effect of strong latitudinal shear in zonal wind. The diurnal variation of airglow emission – which the model simulates well – is related to the vertical advection associated with the tides and downward mixing of atomic oxygen. Highlights: The diurnal variations of the OH and O( 1 S) nighttime airglow in the MLT at Pune, India. This is the only tropical station where the tidal variations of mesosphere and lower thermosphere (MLT) temperature has been observed with ground bases the Spectral Airglow Temperature Imager (SATI). Observations reveal the influence of the dominant migrating semi-diurnal tides during solstice, and diurnal tides during equinox, at this tropical station. The airglow observations are compared with simulations from the Whole Atmosphere Community Climate Model (WACCM). The diurnal variation of airglow emission – which the model simulates well - is related to the vertical advection associated with the tides and downward mixing of atomic oxygen.